11.3% efficiency Cu(In, Ga)(S, Se)2 thin film solar cells via drop-on-demand inkjet printing. Issue 6 (13th May 2016) - Lin, Xianzhong; Klenk, Reiner; Wang, Lan; Köhler, Tristan; Albert, Jürgen; Fiechter, Sebastian; Ennaoui, Ahmed; Lux-Steiner, Martha Ch.
Abstract : Highly efficient Cu(In, Ga)(S, Se)2 thin film solar cells are fabricated using a scalable drop-on-demand inkjet printing approach from environmentally-friendly molecular ink. Abstract : Although Cu(In, Ga)(S, Se)2 (CIGSe) based thin film solar cells have reached efficiencies exceeding 22% based on vacuum processed CIGSSe absorbers, the supply of indium and gallium might become an issue if CIGSSe thin-film solar cells are produced in very large volumes. It is therefore mandatory to reduce the wastage of indium and gallium during the fabrication process. In this work, we report on a highly efficient precursor utilization, and a vacuum-free, and scalable route to the deposition of Cu(In, Ga)(S, Se)2 (CIGSSe) thin films via drop-on-demand inkjet-printing. The precursor ink, which shows long-term stability in air at room temperature, is formulated by dissolving metal nitrate salts in alcohol-based solvents. Crack free CIGSSe absorbers consisting of a layer with large grains at the surface and a layer with small grains at the back have been prepared by annealing the inkjet-printed Cu–In–Ga nitrate precursors in a Se/H2 S containing atmosphere. Ga accumulation has been observed within the layer with small grains. A solar cell with a total area efficiency of 11.3% under standard AM 1.5 illumination has been achieved based on the printed CIGSSe absorbers.